CURRENT RATIO, DEBT, AND ROA EFFECT ON DIVIDEND PAYOUT RATIO AT BEI 2014-2016 PERIOD - Suryati, Deti; Siagian, Arifin (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2024)
The purpose of this research is to figure out if there is the effect of Current Ratio, Debt to Equity Ratio and Return On Assets to Dividend Payout Ratio on Manufacturing companies listed on the Stock Exchange in the period 2014-2016. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange (BEI) in the year 2014 to 2016 is 99 companies. The sample is 39 companies with purposive sampling as the sampling technique. Testing the hypothesis in this research using multiple linear regression analysis. The results show that only Current Ratio significantly influence to Dividend Payout Ratio while Debt To Equity Ratio and Return On Assets not affect to Dividend Payout Ratio. The results also showed that the Current Ratio, Debt to Equity Ratio, Return On Assets simultaneously affect the Dividend Payout Ratio.